2020
DOI: 10.1063/5.0016009
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning Frenkel Hamiltonian parameters to accelerate simulations of exciton dynamics

Abstract: In this manuscript, we develop multiple machine learning (ML) models to accelerate a scheme for parameterizing site-based models of exciton dynamics from all-atom configurations of condensed phase sexithiophene systems. This scheme encodes the details of a system’s specific molecular morphology in the correlated distributions of model parameters through the analysis of many single-molecule excited-state electronic-structure calculations. These calculations yield excitation energies for each molecule in the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…It is worth noting that even though the computational cost of constructing the exciton Hamiltonian through quantum chemistry calculations scales linearly with the number of subunits (assuming that the inter-molecular couplings are negligible beyond certain distance), the computational cost itself is still high for large systems. However, several statistical and machine-learning methods have been developed to overcome this difficulty [46][47][48]. Once sufficient quantum chemistry data have been generated, the remaining matrix elements in the exciton Hamiltonians can be obtained through these statistical or machine learning methods with very high accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that even though the computational cost of constructing the exciton Hamiltonian through quantum chemistry calculations scales linearly with the number of subunits (assuming that the inter-molecular couplings are negligible beyond certain distance), the computational cost itself is still high for large systems. However, several statistical and machine-learning methods have been developed to overcome this difficulty [46][47][48]. Once sufficient quantum chemistry data have been generated, the remaining matrix elements in the exciton Hamiltonians can be obtained through these statistical or machine learning methods with very high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…All the quantum chemical calculations were performed with the PySCF program [52], and density fitting was used with the heavy-aug-cc-pvdz-jkfit auxiliary basis set implemented in PySCF. In estimating the excitonic coupling between the local excitations on two T2 molecules (m and n), V mn , we computed the Coulomb coupling via [46] V…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, it has been shown that the model can represent interaction integrals in localized effective minimal basis representations, which benefits the prediction accuracy for larger systems. 123…”
Section: Please Cite This Article As Doi:101063/50047760mentioning
confidence: 99%
“…The concept of ML-based Hamiltonian and densityfunctional surrogate models directly leads to the construction of approximate electronic structure models based on ML. Recently reported approaches include an ML-based Hückel model, 141 parametrized Frenkel 102,[142][143][144][145] and Tight-binding (TB) Hamiltonians 146 as well as semi-empirical methods with ML-tuned parameters. 147,148 .…”
Section: Please Cite This Article As Doi:101063/50047760mentioning
confidence: 99%
“…For any specific configuration, we compute each value of the intermolecular electronic coupling in an atomistic basis via the point monopole approximation, which has been demonstrated to accurately represent couplings between closely spaced organic dye molecules. 38,39 Specifically, we define the coupling between molecules i and j as,…”
Section: Genetic Algorithm For the Design Of Excitonic Circuitsmentioning
confidence: 99%